2020
DOI: 10.15302/j-laf-1-020030
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media to Explore Perceptions of Ecosystem Services by Nature-Based Solution Projects

Abstract: Introduction 1.1 Nature-Based Solutions and Perceptions of Ecosystem Services Human sustainable development is facing many challenges such as climate change, urbanization, water supply, and disaster risks. Nature-Based Solutions (NBS), which refer to actions inspired by, supported by, or copied from Nature [1] , have been proposed for coping with these challenges. NBS involves directly utilizing the ecosystems with minimum intervention and restoring the ecosystems by following natural laws. These cost-effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The research indicated that a set of ecosystem service functions can consistently cooccur in time and space and could be perceived concurrently. This aligned with conclusions from studies by Jang et al [35], Zhai et al [63], and Wang et al [64]. The Apriori association rule analysis revealed a significant correlation between aesthetic experiences, recreation, and spiritual services.…”
Section: Factors Influencing Visitors' Perception Of Cultural Ecosyst...supporting
confidence: 89%
“…The research indicated that a set of ecosystem service functions can consistently cooccur in time and space and could be perceived concurrently. This aligned with conclusions from studies by Jang et al [35], Zhai et al [63], and Wang et al [64]. The Apriori association rule analysis revealed a significant correlation between aesthetic experiences, recreation, and spiritual services.…”
Section: Factors Influencing Visitors' Perception Of Cultural Ecosyst...supporting
confidence: 89%
“…ESs including habitat, water purification, air purification, noise reduction, flood regulation, recreation, aesthetics, education, and social relations were involved. These examined ESs were selected according to previous studies on perceived ESs in WPs (Zhai and Lange 2020 ). They belonged to the regulating, cultural and supporting category.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, nature-based solutions in urban wetland park land use and planning are a key research trend. Further, research should include a deep exploration of human-nature interactions [96], a consideration of the social value of wetland parks, and the development of new tools and frameworks to achieve the goals of assessing and guiding the design and management of urban wetland parks. Ultimately, achieving these goals requires interdisciplinary collaboration, combining knowledge and methods from different fields such as ecology, social sciences, economics, and urban planning to create sustainable and inclusive urban-development strategies.…”
Section: Land Use: An Area Of Research Focusmentioning
confidence: 99%